Pengaruh Financial Self Control dan Fanatisme Terhadap Perilaku Konsumtif Pada Penggemar NCT di Kabupaten Karawang - Hikmah Fauziyah; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Financial Self Control and Fanaticism on the Consumptive Behavior of NCT fans in Karawang Regency. The descriptive verification method was used with samples selected randomly through simple random sampling, involving respondents who were NCT fans in Karawang Regency. Data collection was carried out using a questionnaire with research instruments that had been tested for validity and reliability. The results of the study based on descriptive analysis showed that Financial Self Control was in the very good category, reflected in the respondents' ability to manage finances and postpone non-urgent purchases. Fanaticism showed a very high category, seen from the enthusiasm and strong emotional attachment to NCT. Consumptive Behavior was in the high category, marked by the tendency to buy both official and unofficial merchandise for emotional satisfaction. Correlation analysis revealed no significant relationship between Financial Self Control and Fanaticism, indicating that the two variables run independently. Partially, Financial Self Control was proven to have a significant negative effect on Consumptive Behavior, indicating that the better a person's financial control, the lower their consumptive behavior. While Fanaticism has a significant positive effect, indicating that the higher a person's fanaticism, the higher the tendency to behave consumptively. Simultaneous analysis shows that Financial Self Control and Fanaticism together have a significant influence on Consumptive Behavior. In conclusion, a high level of fanaticism encourages consumptive behavior, while good financial management can reduce it. These two factors together play an important role in shaping the consumption patterns of NCT fans. Practical implications of the study include the importance of financial education for K-Pop fans to prevent excessive consumptive behavior, including financial management training and understanding of priority needs.